A benzimidazole-based ruthenium(IV) complex inhibits Pseudomonas aeruginosa biofilm formation by interacting with siderophores and the cell envelope, and inducing oxidative stress. Issue 1 (2nd January 2019) - Czerwonka, Grzegorz; Gmiter, Dawid; Guzy, Anna; Rogala, Patrycja; Jabłońska-Wawrzycka, Agnieszka; Borkowski, Andrzej; Cłapa, Tomasz; Narożna, Dorota; Kowalczyk, Paweł; Syczewski, Marcin; Drabik, Marcin; Dańczuk, Magdalena; et al.
Abstract: Pseudomonas aeruginosa biofilm-associated infections are a serious medical problem, and new compounds and therapies acting through novel mechanisms are much needed. Herein, the authors report a ruthenium(IV) complex that reduces P. aeruginosa PAO1 biofilm formation by 84%, and alters biofilm morphology and the living-to-dead cell ratio at 1 mM concentration. Including the compound in the culture medium altered the pigments secreted by PAO1, and fluorescence spectra revealed a decrease in pyoverdine. Scanning electron microscopy showed that the ruthenium complex did not penetrate the bacterial cell wall, but accumulated on external cell structures. Fluorescence quenching experiments indicated strong binding of the ruthenium complex to both plasmid DNA and bovine serum albumin. Formamidopyrimidine DNA N-glycosylase (Fpg) protein digestion of plasmid DNA isolated after ruthenium(IV) complex treatment revealed the generation of oxidative stress, which was further proved by the observed upregulation of catalase and superoxide dismutase gene expression.